Hydrodynamics of Jet-driven Liquid-liquid Inverse Droplet Flow and its Application for Separation of Organic Contaminants - Sangtam, Bongliba T (My University, 2022)
Over the years, the research on the liquid-liquid plunging jet extraction column has drawn significant interest among the scientific fraternity because of its numerous applications, including fine chemical synthesis, recovery of fuel in nuclear plants, acid mixing, ink-jet, and liquid metal transfer (Asadollahzadeh et al., 2016; Gao et al., 2016; Hu et al., 2009; Tadrist et al., 1991). Various researchers have used different columns for the liquid-liquid extraction process such as Kühni column, rotating disc contactor, static mixer, and jet extraction column. Jet mixers have several advantages compared to mechanical mixers because they have low maintenance, low cost, low energy consumption, and shorter mixing time. The jet system has a higher liquid mixing and mass-transfer operation for mixing the liquid-liquid phase. For the past years, the jet device has been employed for wastewater treatment and acid extraction, but the studies were found to be limited. The jet device was used to extract copper ions, and it was discovered that the rate of copper extraction was 7 to 8 times higher than in the CSTR (Dehkordi, 2002a). Suresh et al. (2005) used liquid-liquid jet extraction system and separated uranium and thorium. They have stated that the ejector-type jet device can provide a high extraction efficiency. The various parameters such as liquid-liquid entrainment, drop size and its distribution, axial dispersion coefficient, extraction efficiency, and overall mass transfer play a significant role in designing and modeling of liquid-liquid extraction column. These parameters have an immense impact on selectivity and conversion in chemical engineering applications. Based on the literature, the jet-driven extraction column is gaining popularity for generating interfacial area, intense mass-transfer operations such as gas adsorption, liquid liquid extraction, etc. However, there is a scarcity of studies on hydrodynamics and mass
Majumder, Subrata K
Keywords: CHEMICAL ENGINEERING